2016
DOI: 10.1021/acsami.5b09533
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of ZnO Layers via Hydrogen Plasma Treatment for Efficient Inverted Polymer Solar Cells

Abstract: Modifications of the ZnO electron extraction layer with low-pressure H plasma treatment increased the efficiency of inverted polymer solar cells (PSCs) based on four different photoactive blends, namely, poly(3-hexylthiophene):[6,6]-phenyl C71 butyric acid methyl ester (P3HT:PC71BM), P3HT:1',1″,4',4″-tetrahydro-di[1,4]methanonaphthaleno-[5,6]ullerene-C60 (P3HT:IC60BA), poly[(9-(1-octylnonyl)-9H-carbazole-2,7-diyl)-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl]:PC71BM (PCDTBT:PC71BM), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
1
34
0
3
Order By: Relevance
“…In particular, the estimated exciton lifetimes of PTB7 deposited Figure S15, Supporting Information) verified that charge separation occurring at the ZnO/Al 2 O 3 /P3HT interfaces represents a phenomenon predominantly governed by the suppression of the intrinsic deep defects in ZnO. [34] Finally, all findings in this study explicitly confirm the potential of ALD architecture in regulating the ZnO properties and defect states and verify the significance of ALD-controlled interface engineering in photovoltaic and other optoelectronic applications.…”
Section: Photophysical Properties Of Photoactive Polymers On Zinc Oxidessupporting
confidence: 67%
See 2 more Smart Citations
“…In particular, the estimated exciton lifetimes of PTB7 deposited Figure S15, Supporting Information) verified that charge separation occurring at the ZnO/Al 2 O 3 /P3HT interfaces represents a phenomenon predominantly governed by the suppression of the intrinsic deep defects in ZnO. [34] Finally, all findings in this study explicitly confirm the potential of ALD architecture in regulating the ZnO properties and defect states and verify the significance of ALD-controlled interface engineering in photovoltaic and other optoelectronic applications.…”
Section: Photophysical Properties Of Photoactive Polymers On Zinc Oxidessupporting
confidence: 67%
“…This has the net result of reducing the energy offset between the LUMO of P3HT and the conduction band of ALD-modified ZnO promoting fast, energetically downhill, electron transfer from P3HT to ALD dielectric-coated ZnO, therefore, reducing the exciton lifetime. [34,72] Identically, the simultaneous suppression of defect-induced hole trapping and enhancement of electron transfer in ALD-coated ZnO granted minor deviations in exciton lifetimes of 40 nm thick PTB7 films deposited on ZnO substrates; this was estimated from TRPL measurements for excitation at 468 nm and detection at 790 nm (Figure 6c; Table S3, Supporting Information) and 830 nm (Figure 6d; Table S4, Supporting information). In particular, the estimated exciton lifetimes of PTB7 deposited Figure S15, Supporting Information) verified that charge separation occurring at the ZnO/Al 2 O 3 /P3HT interfaces represents a phenomenon predominantly governed by the suppression of the intrinsic deep defects in ZnO.…”
Section: Photophysical Properties Of Photoactive Polymers On Zinc Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][51][52] Besides the metal and also nitrogen doping which has also been reported to tune the properties of the zinc oxide surface, 53 our group and others recently introduced the beneficial surface modification of ZnO by using a hydrogen (H) plasma treatment for efficient inverted PSCs. 54,55 Plasma surface treatment is a process that alters the surface energy of many materials so as to improve the bonding characteristics. In our previous work it was found that H plasma treatment altered the surface properties of ZnO films, in particular the wetting of the photoactive layer, while it also reduced surface roughness and induced significant changes in the nanomorphology/crystallinity of the photoactive blend, which was deposited on top of the ZnO surface, allowing efficient charge generation and extraction.…”
Section: Introductionmentioning
confidence: 99%
“…However, ZnO thin films derived via the sol‐gel method have more unreacted organic residuals and other chemical defects than those derived via other high‐temperature methods such as magnetron sputtering, spray pyrolysis, or molecular beam epitaxy . Therefore, various surface treatment methods have been developed to decrease the surface defects of solution‐processed ZnO and realize high‐performance organic diodes . The representative examples introduce nanoparticle ZnO doped with thiophene, sulfur, or Cs in colloid phases, which result in enhanced organic photovoltaic performances as the electron transport layer.…”
Section: Introductionmentioning
confidence: 56%